Betula nana shrub-ring carbon isotopes ... - Sullivan, Patrick (NSF Arctic Data Center, 2016)
Carbon isotope discrimination in alpha-cellulose of Betula nana growth rings. Measurements were made in support of Cassandra Gamm's M.S. thesis at the University of Alaska Anchorage. The goal was to examine potential increases in moisture limitation of shrub growth over time. ...